Edukasi Peningkatan Kemampuan Kader dalam Mengenali Tanda Penyakit Infeksi Pascabencana di Desa Beuringen Pidie Jaya (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Hydrometeorological disasters increase the risk of infectious diseases due to environmental changes, damaged sanitation systems, and limited access to health services. These conditions highlight the need to strengthen community-based early detection systems as part of an early warning strategy. This community service activity aims to enhance the capacity of community health volunteers in the early detection and reporting of infectious diseases through the digitalization of a simple surveillance system. The program was implemented in disaster-affected areas, involving community health volunteers as key partners. The methods included health education on post-disaster infectious diseases, technical training on the use of surveillance instruments, and assistance in implementing health surveillance forms in accordance with guidelines from the Ministry of Health of the Republic Indonesia. The results showed a significant improvement in the knowledge of participants, with ≥80% of volunteers passing the post-test evaluation. In addition, participants demonstrated improved skills in recording, identifying symptoms, and systematically reporting infectious disease cases. The digitalization of surveillance forms facilitated real-time data collection and reporting, enabling faster responses to potential outbreaks. This program contributes to strengthening community-based early warning systems and enhancing the role of community health volunteers as the frontline in post-disaster infectious disease control. The implementation of this initiative is expected to support rapid interventions by health service facilities, improve cross-sector coordination, and serve as a replicable model for strengthening community surveillance systems in other disaster-prone areas.